Triphenylamine-based organic small-molecule interlayer materials for inverted perovskite solar cells - Doyranli, Ceylan; Choi, Fatma Pinar Gokdemir; Alishah, Hamed Moeini; Koyuncu, Sermet; Gunes, Serap; San, Nevim (ELSEVIER, 2022)
In this report, two novel donor-acceptor-donor type triphenylamine-quinoxaline-based (QC-TPA and QC-TPAOMe) small organic molecules have been synthesized by the Suzuki coupling reaction as hole transport materials (HTMs) and successfully utilized in the NiOx/perovskite interface. All device fabrication steps with ITO/NiOx/QC-TPA or QC-TPAOMe/CH3NH3PbI3/PCBM/BCP/Ag configurations were performed in ambient air over 55% relative humidity, except for thermal evaporation of metal contacts. Modifications of the NiOx/ perovskite interface with QC-TPA and QC-TPAOMe molecules can improve FF and JSC by enhancing hole extraction and reducing energy losses. Consequently, the power conversion efficiency (PCE) boosted from 10.03% to 14.46% and 13.21% with surface modifications of NiOx with QC-TPA and QC-TPAOMe, respectively.
Keywords: Hole transport layer; Inverted perovskite solar cells; Interlayer materials; Donor-acceptor-donor type organic small; molecules; HOLE-TRANSPORTING MATERIALS; SURFACE MODIFICATION; INTERFACIAL LAYER; LOW-COST; OXIDE; PERFORMANCE; EFFICIENT; DEFECT; AIR; Materials Science; Physics